Taxation and Conditional Cooperation - Bruno S. Frey; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2004)
Why so many people pay their taxes, although fines and audit probability are low, has become a central question in the tax compliance literature. Concepts of Homo Economicus, endowed with a more refined motivation structure, help to shed light on the tax compliance puzzle. This paper provides empirical evidence for the relevance of conditional cooperation, using survey data from 30 European countries. The findings suggest that a higher perceived tax evasion leads to a lower tax morale, also when controlling for additional factors in a multivariate analysis.
Keywords: H26; H73; D64; 330; tax morale; tax compliance; tax evasion; pro-social behavior